Recurrence and influencing factors of moderate-to-severe atopic dermatitis after dupilumab withdrawal: a retrospective cohort analysis - Chen, Maohua; Wen, Xinyu; Liu, Jie; Yang, Ge; Li, Qingqing; Jiang, Zhiyuan; Zhang, Xinjie; Cai, Zhen; Zhang, Lixia (Frontiers in Medicine, 2025)
BackgroundAtopic dermatitis (AD) is a chronic, recurrent, inflammatory skin disease. Although dupilumab has demonstrated favorable efficacy in the treatment of patients with moderate-to-severe atopic dermatitis, data on its recurrence after discontinuation remain limited.ObjectiveTo explore the recurrence rate, time to recurrence, and factors influencing recurrence in patients with moderate-to-severe AD after discontinuing dupilumab, to bridge the existing knowledge gap and provide a reference for promoting long-term standardized management of the disease in AD patients to reduce AD recurrence.MethodsPatients with moderate-to-severe AD treated with dupilumab between January 2021 and December 2023 at Sichuan Provincial People’s Hospital were included. All patients started from the time of drug discontinuation, and baseline characteristics of patients were collected from all enrolled patients, and follow-up visits were conducted every 2 weeks after drug discontinuation utilizing telephone or medical records. Descriptive statistics summarized the relapse rate and time to relapse, and the Cox proportional hazards model was applied to determine the predictive factors of relapse after discontinuing dupilumab.ResultsBy the follow-up cut-off time, the median follow-up time was 49 weeks (24–85 weeks), and 141 AD patients were finally included in the statistical analysis. Of the 141 patients, 33 patients relapsed, with a relapse rate of 23.4% (95% CI, 16–30%), and the median time to relapse was 29 weeks. Predictors with a significant effect on recurrence included allergic conjunctivitis (HR = 7.912, 95% CI, 1.280–48.895, p = 0.026), duration of treatment <16 weeks (HR = 5.871, 95% CI, 2.154–16.003, p = 0.001), BMI ≥ 28 (HR = 5.653, 95% CI, 2.331–13.713, p < 0.001), male (HR = 5.634, 95% CI, 1.727–18.373, p = 0.004), and positive familial predisposition to allergy (HR = 3.438, 95% CI, 1.351–8.747, p = 0.01).ConclusionThe cumulative recurrence rate in 141 AD patients was 23.4%; the median time to recurrence in 33 AD recurrence patients was 29 weeks (22–59 weeks); comorbid allergic conjunctivitis, treatment duration shorter than 16 weeks, obesity, male patients, and positive familial predisposition to allergy were independent risk factors for AD recurrence. These findings confirm the disease characteristic of AD’s susceptibility to relapse and emphasize the need for individualized treatment, post-discontinuation monitoring, and long-term standardized management of AD patients with different risk factors for relapse.